A Comparative Study of Lipid Profile among Smokers and Non Smokers - Byar, Nabin Kumar; Shrestha, Tirtha Man; Pratap, Narayan Prasad; Khanal, Santosh (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Smoking is a risk factor for the development of cardiovascular diseases and many other diseases. Smoking is found to alter lipid profile and poses a risk for atherosclerosis. This study aims to compare lipid profile between smokers and non smokers. Methods: Hospital based observational study was carried out in Tribhuwan University, Teaching hospital(TUTH), Kathmandu, Nepal on 90 smokers and 90 non smokers who were apparently healthy. Data on socio demographic variables were collected using a questionnaire and lipid profile was estimated on fasting venous blood in an auto-analyzer. The lipid levels of smokers and non smokers were compared using t-test. Results: Most of the smokers were daily wagers and they consumed alcohol and high fat food compared to non smokers. The serum levels of HDL were significantly lower in smokers compared to nonsmokers.LDL level was positively correlated with numbers of cigarettes/ beedi smoked. The LDL level was significantly high in those who smoked more than 10 cigarettes or beedis. The duration of smoking had no significant effect on lipid profile. LDL and VLDL were significantly high among those with pack years more than 3. LDL levels positively correlated with pack year. Conclusion: Tobacco smoking is associated with dyslipidemia (increased LDL-c and decrease HDL-c level.